Scholars and sultans in the early modern Ottoman empire revisiting the divergence of the NCVS and UCR - Atcil, Abdurrahman (Cambridge University Press, 2007)
This book examines the transformation of scholars into scholar-bureaucrats and discusses ideology, law and administration in the Ottoman Empire.